GUM industries (1985) Sdn. Bhd.- the Totoya crisis - Teoh, Kenny Guan Cheng; Yee, Choy Leong; Mohamed, Zainal Abidin; Tan, Mei Fatt (Universiti Putra Malaysia Press, 2008)
This case on strategy presents an opportunity for post-graduate and final year undergraduate students to try their hands at crisis management. It provides critical information on the organization’s internal and external environment and highlights issues that require their immediate attention. To emulate reality, a sense of urgency has been written into the case. This case has a moderate level of difficulty. The case may also be used to teach marketing, especially in terms of value creation along the supply chain, from suppliers to end consumers.